Deciphering the role of glycine betaine in enhancing plant performance and defense mechanisms against environmental stresses - Basit, Farwa; Alyafei, Mohammed; Hayat, Faisal; Al-Zayadneh, Wasef; El-Keblawy, Ali; Sulieman, Saad; Sheteiwy, Mohamed S. (Frontiers in Plant Science, 2025)
In the context of climate change, abiotic stresses are recognized as significant environmental challenges that limit agricultural productivity globally. These conditions disrupt normal plant growth and development processes. The ability of plants to tolerate these stressors is linked to their resilience mechanisms. Glycine betaine (GB), also known as betaine, is a derivative of methylated glycine identified in numerous plant species as a substance that mitigates the detrimental effects of stressful environments. GB is synthesized in the cytosol as an initial response to abiotic stress, and signaling molecules, such as jasmonic acid and methyl jasmonate, primarily initiate its production. Recent studies have highlighted their role in stimulating GB synthesis and its subsequent accumulation. The concentration of GB within a plant system can effectively indicate tolerance levels, ultimately contributing to the understanding of resilience mechanisms. GB plays a crucial role in reducing the accumulation and detoxification of reactive oxygen species (ROS), which aids in restoring photosynthesis and alleviating oxidative stress. It contributes to the stabilization of membranes and macromolecules and is essential for the protection and stabilization of photosynthetic components, such as ribulose-1,5-bisphosphate carboxylase/oxygenase, photosystem II, and quaternary enzyme and protein complex structures, under environmental stress conditions. Furthermore, GB can enhance stress tolerance even at minimal concentrations by activating the genes associated with stress defense mechanisms. Recent studies have demonstrated that the application of GB can protect against environmental challenges, thereby improving both crop yield and quality. This review concentrates on the role of GB in promoting abiotic stress tolerance and explores potential strategies for engineering GB biosynthesis in plants.